2016
DOI: 10.1007/s12020-016-0930-9
|View full text |Cite
|
Sign up to set email alerts
|

AIP mutations in young patients with acromegaly and the Tampico Giant: the Mexican experience

Abstract: Although aryl hydrocarbon receptor-interacting protein (AIP) mutations are rare in sporadic acromegaly, their prevalence among young patients is nonnegligible. The objectives of this study were to evaluate the frequency of AIP mutations in a cohort of Mexican patients with acromegaly with disease onset before the age of 30 and to search for molecular abnormalities in the AIP gene in teeth obtained from the "Tampico Giant". Peripheral blood DNA from 71 patients with acromegaly (51 females) with disease onset <3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
14
1
3
Order By: Relevance
“…In the FIPA setting, AIP pathogenic variants are demonstrated in about 20% of families, while in cohorts of unselected apparently sporadic pituitary adenomas AIP pathogenic variants are rarely found -in less than 4% (11,84). However, in young adults (diagnosed < 30 years of age) with apparently sporadic adenomas (mostly macroadenomas), the prevalence of AIP pathogenic variants was higher, ranging between 1.6 and 13% (85,86,87,88,89,90,91,92,93). Further decreasing the age of diagnosis (pediatric/ adolescent patients <18 year/old) increases the frequency of AIP pathogenic variants to 11-25% (85,87,94,95,96,97,98).…”
Section: Aip Mutations In Fipa and Sporadic Pituitary Adenomasmentioning
confidence: 99%
“…In the FIPA setting, AIP pathogenic variants are demonstrated in about 20% of families, while in cohorts of unselected apparently sporadic pituitary adenomas AIP pathogenic variants are rarely found -in less than 4% (11,84). However, in young adults (diagnosed < 30 years of age) with apparently sporadic adenomas (mostly macroadenomas), the prevalence of AIP pathogenic variants was higher, ranging between 1.6 and 13% (85,86,87,88,89,90,91,92,93). Further decreasing the age of diagnosis (pediatric/ adolescent patients <18 year/old) increases the frequency of AIP pathogenic variants to 11-25% (85,87,94,95,96,97,98).…”
Section: Aip Mutations In Fipa and Sporadic Pituitary Adenomasmentioning
confidence: 99%
“…We demonstrate that all 18 R304 * ‐positive pedigrees of Irish origin identified in the study inherited this allele from a common ancestor, the R304 * founder. In addition, we have shown that R304 * in pedigrees of English, Indian, Romanian, US Italian, Irish, and Mexican origin derives from independent recurrent mutational events [Chahal et al., ; Ramirez‐Renteria et al., ]. Founder AIP mut alleles have also been identified through haplotype analysis in Finnish [Vierimaa et al., ], Italian [Occhi et al., ], Comoros [Cuny et al., ], and English [Salvatori et al., ] populations, involving the p.Q14 * , p.R304 * , p.G117Afs * 39, and p.F269_H275dup alleles, respectively, but the present population frequency of all these founder alleles remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Two-thirds of the AIP mutations lead to protein truncations, which remove segments of the TPR domains and/or carboxy-terminal end, and therefore, lead to loss of function of the protein 62,64,65 . A common genetic "hotspot" for mutations in the AIP protein is the 304 residue (R304X and R304Q), which affects a CpG sequence and has been shown to be present in several independent families from different parts of the world [65][66][67][68] . Other potential hotspots include the 271 and the 81 loci (65)(66).…”
Section: Familial Isolated Pamentioning
confidence: 99%
“…Inactivating AIP mutations are responsible for 20% of FIPA cases 62,65 . Germline, heterozygous AIP mutations are also present in 5-10% of cases of sporadic GH-secreting adenomas [65][66][67] . Acromegaly patients with AIP mutations are usually diagnosed before age 30, usually harbor macroadenomas, frequently cosecrete prolactin and appear to be somewhat less responsive to treatment with somatostatin analogs [65][66][67] .…”
Section: Familial Isolated Pamentioning
confidence: 99%